The Influence of English Communication Proficiency on Personal Branding and Career Pathways of English Department Alumni in National Companies - Yoga Pratama; Dasmo Dasmo; Suranto Suranto; Fridolini Fridolini; Celerina Dewi Hartati (Jurnal Pemberdayaan Masyarakat, 2026)
This systematic literature review examines the effectiveness of Problem-Based Learning (PBL) e-modules in developing students' 21st-century skills by synthesizing ten Scopus-indexed empirical studies published between 2015 and 2025. Motivated by the growing demand for student-centered and technology-integrated learning, this review aims to consolidate evidence on how PBL-oriented digital modules support key competencies. Following the PRISMA guidelines, the study employed a transparent selection process and combined thematic synthesis with bibliometric analysis (VOSviewer) to identify research trends, dominant themes, and learning outcomes. The findings indicate that PBL e-modules consistently enhance critical thinking, collaboration, communication, and creativity, with the strongest effects reported in critical thinking and collaborative performance. Student motivation and autonomy emerged as important mediating factors, while variations in instructional design and digital platform quality influenced effectiveness across contexts. These results imply that well-structured PBL design and purposeful digital integration are critical for maximizing the impact of e-modules on 21st-century skills, while also highlighting methodological gaps for future research.